Living into the life of Jesus the formation of Christian character - Issler, Klaus Dieter (Downers Grove, Ill. : IVP Books, 2012)
Klaus Issler derives insights from the life of Jesus in the Gospels to uncover the dynamics of becoming Christlike. You will discover how you can forge much deeper connections with Jesus so that his life begins to permeate your own character. --from publisher description
Form your heart, not just your behavior -- Wake up to five formation gaps -- Adapt formation practices for your journey -- Love: divine relational support in Jesus' life and ours -- Holy spirit: divine mentoring in Jesus' life and ours -- Scripture: divine revelation of reality and a "Jesus" lifestyle -- Three exemplary Jesus practices about relationships -- Three exemplary Jesus practices about money and work.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Spiritual formation; Character -- Religious aspects -- Christianity; Jesus Christ -- Example; RELIGION / Christian Life / General; Electronic books